Resource Misallocation and Productivity : Evidence from Mexico - Misch, Florian; Saborowski, Christian (Washington, D.C. : International Monetary Fund, 2018)
This paper explores the role for specific structural distortions in explaining Mexico's weak productivity growth through the resource misallocation channel. The paper makes two contributions. First, we validate the approach of measuring misallocation indirectly (Hsieh and Klenow, 2009) by illustrating a close correlation between misallocation and per capita incomes across Mexican states. Second, we exploit the large variation in resource misallocation within industries and across states together with unusually rich data at the firm, local, and industry level to shed light on its determinants. We identify several well-defined distortions that have a statistically and economically meaningful effect on productivity via resource misallocation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet